PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS Va SD NEGERI 126 PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study aims to improve the process and improve learning outcomes of students with the application of mathematics learning Problem Based Learning (PBL) in the class Va Pekanbaru Elementary School 126 School Year 2014/2015 on the Basic Competency Standards Using Fractions in troubleshooting. The subject of this research were 22 students with 11 male students and 11 female students with heterogeneous capabilities. This research is a classroom action research (PTK), which consists of two cycles. Data collection techniques in this study was done by using observation and tests. Sheet observations will be analyzed by descriptive narrative that aims to describe the activities of students and teachers during the learning process takes place, while the achievement test will be analyzed with criteria mastery Minimum (KKM) and analysis of average value, to determine whether or not an increase in results learners before and after the application of the learning model Problem Based Learning (PBL). The results show an increase in mathematics learning outcomes Va grade students of SD Negeri 126 Pekanbaru. It also is also seen in the activities of teachers at each petemuan increasingly visible from the average percentage of the first cycle of the first meeting was 70% and at a meeting II to 80% and the percentage of the second cycle of the first meeting were 90% and meeting II to 95%, while average analysis of learning outcomes of students on the basis of scores, daily tests daily tests I and II, where the average value of the study of students at the basic score is 59.0, while the first daily test average value of learning outcomes of students is 63.2 as well as the daily test II, the average value of learning outcomes of students 77.3. From the research, it can be concluded that the application of the model of Problem Based Learning (PBL) can improve students' mathematics learning outcomes Va grade Elementary School 126 Pekanbaru.Keywords : Learning Application of Problem Based Learning (PBL), Math Learning Outcomes